Physical Status and Psychosocial Wellbeing of Child Domestic Workers in Selected Wards of Pokhara - Banstola, Ratna Shila; Paudel, Usha Kiran; Shrestha, Romina (Journal of Institute of Medicine Nepal, 2025)
Introduction: Child domestic workers (CDWs) face unique physical and psychosocial challenges; however, research on these issues is limited. This study assesses the nutritional status, physical health, and psychosocial problems among CDWs in selected wards of Pokhara. Methods: A cross-sectional study was conducted among 125 CDWs using a snowball sampling. Data were collected via semi-structured interviews and physiological measurements. Descriptive statistics (frequency, percentage, mean, and standard deviation) and inferential statistics (Chi-square test) at a 5% significance level were used. Odds ratios were calculated at a 95% confidence interval. Data analysis was performed using SPSS version 16. Results: Among the CDWs, 50.9% reported inadequate fulfilment of basic needs; 50.4% exhibited stunted stature, 35.2% had low weight for age, and 16.8% were underweight based on BMI. Male CDWs (p = 0.001, OR = 4.929) and those obtaining less than seven hours of sleep per night (p = 0.003, OR = 5.77) demonstrated significantly greater odds of being underweight. Health problems were reported by 47.2%, while 50.9% had sustained work-related injuries. Older CDWs (p = 0.011, OR = 2.679) were significantly more likely to report health problems. Psychosocial problems were observed in 25.6% of the CDWs and were significantly associated with working over eight hours daily (p = 0.036, OR = 2.450), inadequate fulfilment of basic needs (p = 0.002, OR = 3.868), and dissatisfaction with work (p = 0.003, OR = 3.471). Conclusions: Poor nutrition among child domestic workers was associated with inadequate sleep and male sex; health and psychosocial problems correlated with older age, long hours, unmet needs, and dissatisfaction, warranting further longitudinal research.